Crop Adaptation to Elevated CO2 and Temperature - Bunce, James (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book contains a collection of recent peer-reviewed articles on the topic "Crop Adaptation to Elevated CO2 and Temperature" published in Plants. Topics range from meta-analyses of crop responses, to descriptions and results of large-scale screening efforts, to molecular studies of changes in gene expression related to fruit quality.